Tumor Microenvironment-Responsive Polymeric iRGD and Doxorubicin Conjugates Reduce Spontaneous Lung Metastasis in an Orthotopic Breast Cancer Model - Zheng-Hong Peng; Chinmay M. Jogdeo; Jing Li; Ying Xie; Yazhe Wang; Yuri M. Sheinin; Jindřich Kopeček; David Oupický (MDPI AG, 2022)
Tremendous progress has been made in the field of nanomedicine for cancer treatment. However, most of the research to date has been focused on inhibiting primary tumor growth with comparatively less efforts directed towards managing tumor metastasis. Here, we introduce a polymeric conjugate P-DOX-iRGD that not only significantly suppressed primary tumor growth but also substantially inhibited pulmonary metastasis in an orthotopic mouse model of breast cancer. In addition, treatment with P-DOX-iRGD markedly reduced breast cancer-induced splenomegaly and liver hematopoiesis. Interestingly, contrasting results were seen for the free form and polymeric form of DOX in vitro and in vivo, which may be attributed to the enhanced permeability and retention (EPR) effect.